Semi Perfect Disconnected Domination Number in Fuzzy Graphs - S. Basheer Ahamed, M. Mohamed Riyazdeen (International Journal of Modern Agriculture, 2020)
A subset Dspd(G) of V is said to be a semi perfect disconnected dominating set if Dspd(G) is perfect, < Dspd(G)> is disconnected and < V ̶ Dspd(G)> is connected. The fuzzy perfect disconnected domination number gspd(G) is the minimum fuzzy cardinality taken over all minimal semi perfect disconnected dominating sets of G.